Case Report of Jingyun Platform's Cognitive Training on Cognitive Impairment with Aphasia - Yu ZHOU; Zhuoming CHEN; Hantian GUAN; Chaoping OUYANG (康复学报)
Objective:To observe the curative effect of Jingyun platform's cognitive training on cognitive impairment with aphasia.Methods:A case of cognitive impairment with aphasia was collected, and ABBA model was used to design a case in-subject. Traditional cognitive training stage was A stage, and the traditional cognitive training was based on the artificial development and implementation of the cognitive training content according to the cognitive impairment points of the case. Jingyun platform's cognitive training stage was B stage, the cognitive training design was adopted according to the functional impairment of the case, and the automatic, intelligent and interesting training was conducted. The ABBA balance sequence was used for the intervention of the case, and the intervention process was divided into six stages, including pretreatment, traditional cognitive training, Jingyun platform cognitive training, blank stage, Jingyun platform cognitive training and traditional cognitive training. Patients received admission examination before treatment, received the traditional cognitive training in stage of traditional cognitive training for five days a week, received Jingyun platform's cognitive training in stage of Jingyun platform's cognitive stage, and stopped the cognitive training in blank stage. The time of Jingyun platform cognitive training was supervised by researchers via network. Each stage lasts for six weeks, 30 minutes at a time, twice a day. The total score of MoCA, subitem score in MoCA, the correct number of words in memory and delayed recall, total time of MoCA evaluation and time-consuming changes in memory were calculated.Results:Compared with before treatment, the memory and delayed recall in traditional cognitive training stage and Jingyun platform cognitive training stage were improved. After the cognitive training of Jingyun platform, the MoCA total score was higher than that of traditional language cognitive training stage, especially in attention, delayed recall and directional subitems. There was no significant improvement in the language, and visual space, execution and naming which remained normal in all stages. Compared with the first stage of traditional cognitive training, the correct number of the first memory of MoCA was improved in the first stage of cognitive training of Jingyun platform, and the first and second memory were at normal level in the second stage of traditional cognitive training and Jingyun platform cognitive training. Moreover, delayed recall (no hint) in the first and second stages of the cognitive training of Jingyun platform was higher respectively than that of traditional cognitive training stage. Compared with before treatment, the total time of MoCA, and the time-consuming of memory (the first time) and delayed recall (no hint) in traditional cognitive training stage and Jingyun platform cognitive training stage were shortened. Moreover, compared with traditional cognitive training stage, the total time-consuming in MoCA evaluation, memory (the first time) and delayed recall (no hint) in Jingyun platform cognitive training stage were significantly shortened.Conclusion:Both traditional cognitive training and Jingyun platform cognitive training can improve the cognitive rehabilitation in the case. Compared with traditional cognitive training, Jingyun platform is move effective in improving the cognition with its precise training system, and has certain advantages in response, attention, memory and in the directional improvement.